Crisis of Sovereignty: Legal Challenges in Delivering Humanitarian Assistance to Conflict Zone - Puspoayu, Elisabeth Septin; Widagdo , Setyo; Kusumaningrum, Adi; Kurniaty, Rika (Jurnal Suara Hukum, 2025)
The emergence of new actors as subjects of international law presents a new challenge in the application of humanitarian law. During armed conflict, the civilian population is not a party to the war and must therefore be protected. One of the forms of protection that must be applied is the provision of humanitarian assistance. The issue of the provision of humanitarian assistance in situations of armed conflict is contingent upon the concept of state sovereignty. This article will examine the relationship between humanitarian assistance and sovereignty, as well as the obstacles to state consent to provide humanitarian assistance in international armed conflicts. In order to address this issue, this article presents a comprehensive explanation based on a normative and case-specific approach to the legal framework governing corporations in international law, with a particular focus on humanitarian law. This article His research highlights the complex relationship between state sovereignty and humanitarian assistance in armed conflicts. Sovereignty obligates states to protect civilians, yet international law, particularly the Fourth Geneva Convention (1949), mandates the non-discriminatory provision of aid. When a state cannot or refuses to assist its population, it must permit external aid. Failure to do so may justify international intervention, balancing sovereignty with humanitarian imperatives.